INTEGRATION OF PERSONALIZED, IMMERSIVE, AND MEMORABLE DIGITAL MARKETING INTO CAREER SERVICES FOR TOURISM STUDENTS - Safitri Safitri; Musafa Musafa (Jurnal Konseling Pendidikan Islam, 2026)
The dynamic and experience-based nature of the tourism industry requires higher education graduates to possess comprehensive career readiness, encompassing not only technical competencies but also strong career engagement and meaning-making. However, career guidance services in higher education remain largely informational and insufficiently experience-oriented. This study aims to analyze the effects of integrating digital-based personalized, immersive, and memorable marketing approaches into career guidance services on career engagement and career readiness among tourism students. This study employed a quantitative survey design involving undergraduate students enrolled in tourism-related programs at higher education institutions. Data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) to examine the relationships among variables. The findings indicate that digital-based personalized, immersive, and memorable marketing significantly and positively influence students’ career engagement. Furthermore, career engagement was found to have a significant effect on career readiness and to function as a mediating variable that strengthens the influence of the three approaches. Among the three approaches, immersive marketing demonstrated the strongest effect on career engagement. These results highlight the importance of developing career guidance and counseling services that emphasize experiential learning, personalization, and emotional meaning through the effective use of digital technologies. Practically, this study provides valuable implications for higher education institutions and career counselors in designing innovative, adaptive, and student-centered career services to enhance graduates’ readiness to enter the tourism workforce.